2010
DOI: 10.1158/0008-5472.can-09-4272
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic Acid as a New Adjuvant Therapeutic Strategy for Ewing's Sarcoma Patients

Abstract: Ewing's sarcoma (ES) is the second most frequent pediatric bone tumor also arising in soft tissues (15% of cases). The prognosis of patients with clinically detectable metastases at diagnosis, not responding to therapy or with disease relapse, is still very poor. Among new therapeutic approaches, bisphosphonates represent promising adjuvant molecules to chemotherapy to limit the osteolytic component of bone tumors and to protect from bone metastases. The combined effects of zoledronic acid and mafosfamide were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 36 publications
2
66
0
Order By: Relevance
“…ZA has attracted recent interest as a non-cytotoxic anticancer drug and is under clinical investigation for use in various diseases, including primary bone tumors (3,4,(7)(8)(9). Promising features of ZA include the observed anticancer synergies between bisphosphonates and cytotoxic chemotherapies (4,30), the favorable toxicity profile, and the proposed effect on the tumor-promoting bone/bone marrow microenvironment to prevent dissemination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ZA has attracted recent interest as a non-cytotoxic anticancer drug and is under clinical investigation for use in various diseases, including primary bone tumors (3,4,(7)(8)(9). Promising features of ZA include the observed anticancer synergies between bisphosphonates and cytotoxic chemotherapies (4,30), the favorable toxicity profile, and the proposed effect on the tumor-promoting bone/bone marrow microenvironment to prevent dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Promising features of ZA include the observed anticancer synergies between bisphosphonates and cytotoxic chemotherapies (4,30), the favorable toxicity profile, and the proposed effect on the tumor-promoting bone/bone marrow microenvironment to prevent dissemination. However, drug therapy alone is unlikely to completely eliminate residual disease in patients with high-risk disseminated tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…43,44 Although no negative effect on osteoblasts has been reported yet, little is known about the role of ZA in regulating osteoblast functions. Interestingly, recent reports showed that ZA could induce BSP expression directly in osteoblast-like cells through inactivation of Rho GTPases 45,46 Although it was beyond the scope of this study, our model would also be useful for further characterization of the mechanism of action of ZA in osteoblasts and for studies of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%